Transparency and Accountability: What If the Federal Gainful Employment—Debt Measures Rules Applied to Law Schools? (Perspectives on Legal Issues in Education) - Kari Ann Mattox (Educational Considerations, 2013)
The purpose of this analysis is to compare current guidelines of the American Bar Association (ABA) for law schools to those of the U.S. Department of Education’s Gainful Employment-Debt Measures regulations in order to assess their transparency and accountability.
Keywords: law schools; Department of Education; Gainful Employment-Debt Measures; regulations; Higher Education; American Bar Association(ABA); standards; benchmark; employment; federal; taxpayer